Evaluation of an immunochromatographic strip test for alpha‐thalassaemia screening. (17th August 2018) - Bunkall, Carolyn; Ghallyan, Nikhil; Elliott, Catherine; Van de Water, Neil; Chan, George
Abstract: Introduction: Hb H inclusion test (HbH‐i) commonly used for α‐thalassaemia screening is not standardised and is labour‐intensive. This study evaluated a strip test based on immunochromatographic detection of Hb Bart's (ICT) for use as a routine screening test for α‐thalassaemia screening in the clinical laboratory setting. Methods: The performance characteristics of the ICT was determined by comparing the results of ICT and HbH‐i on 67 patients, and the α‐globin genotype on 47 of these patients who also had the molecular analysis. Specimen stability was tested on 16 specimens with the ICT repeated after 7 days of storage. The age of babies from which the ICT result becomes valid was determined on 49 samples with patient age ranged from 4 weeks to 12 months. Results: The ICT had higher overall sensitivity of 76% compared to 24% for HbH‐i in detecting carriers of α‐thalassaemia mutations, and this is seen in all α‐thalassaemia genotypes. The test could be carried out on specimens stored at 4°C for 7 days and gave valid results with no false positive from the age of 6 months onwards. It required no special technical expertise or equipment and gave the result in less than 5 minutes. Conclusion: The ICT is simple to perform, with higher sensitivity than HbH‐i, and gives the result in a short time and at a lower cost. This can be used by clinical laboratories to replace HbH‐i for α‐thalassaemia detection.